2008
DOI: 10.1179/136485908x355247
|View full text |Cite
|
Sign up to set email alerts
|

Giardiainfections in Cuban children: the genotypes circulating in a rural population

Abstract: Stool samples containing Giardia duodenalis cysts were collected from 95 primary-school children in central Cuba, and preserved by storing at -20 degrees C in 70% ethanol. Clinical data were collected for each child. Although 57% of the children were asymptomatic, the remaining 43% each reported between one and three symptoms. Following cyst quantification and isolation, molecular analyses were attempted on all cyst isolates, with the focus on the parasite's beta-giardin and glutamate-dehydrogenase (gdh) genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
3
37
2
1
Order By: Relevance
“…Likewise, in elementary school children in Saudi Arabia, all infections with assemblage B were symptomatic, while only subassemblages AI and AII were found in asymptomatic infections (12). It was also noticed that symptomatic giardiasis was more significantly associated with assemblage B in children and adults in Ethiopia (87) and elementary school children in Cuba (202).…”
Section: Molecular Epidemiology Of Giardiasis In Humansmentioning
confidence: 66%
See 1 more Smart Citation
“…Likewise, in elementary school children in Saudi Arabia, all infections with assemblage B were symptomatic, while only subassemblages AI and AII were found in asymptomatic infections (12). It was also noticed that symptomatic giardiasis was more significantly associated with assemblage B in children and adults in Ethiopia (87) and elementary school children in Cuba (202).…”
Section: Molecular Epidemiology Of Giardiasis In Humansmentioning
confidence: 66%
“…High infection rates for giardiasis have been reported for developing countries, and some recent data are listed in Table 2. In various Asian countries (Bangladesh, Cambodia, China, India, Indonesia, Laos, Malaysia, Nepal, Philippines, Thailand, Turkey, Saudi Arabia, and Vietnam), North America (Cuba, Mexico, and Nicaragua), South America (Argentina, Brazil, Colombia, and Peru), and Africa (northern Africa, west Africa, and South Africa), most of the studies focused on children, and infection rates for G. duodenalis fell into the range of 8% to 30% in the majority of those studies (12,29,56,62,63,65,69,144,160,166,174,184,186,202,203,229,234,237,239,252,253,281). In a few studies, the infection rate was lower than 4% or higher than 30% (65,137,145,230,243,274,280).…”
Section: Public Health Importance Of Giardiasismentioning
confidence: 99%
“…The severity of the disease is likely determined by the interplay between the parasite virulence and the developmental, nutritional, and immunological status of the host. Studies conducted until now have been discordant; some authors have reported an association between assemblage A and symptoms (2,16,28,30,31), while others have pointed to an association between assemblage B and symptoms (12,18,29). Almost all of these studies were based on the analysis of a single gene, and it is interesting that genotyping at the ssu-rRNA and tpi genes supports the assemblage A-symptoms association, whereas genotyping at the ␤-giardin and gdh genes supports the assemblage B-symptoms association.…”
Section: Discussionmentioning
confidence: 97%
“…Este resultado concuerda con lo observado en otros países americanos, como Nicaragua, Brasil, Perú y Argentina (19,26,31,32), en donde se han encontrado también los dos genotipos circulando entre los aislamientos provenientes de las personas analizadas, con valores equiparables a los hallados en Cuba, con nueve aislamientos del genotipo A (45 %) y 11 del genotipo B (55 %) (33).…”
Section: Figuraunclassified